Organizational behavior and its role in creating an organizational culture for managing the diversity of human resources in organizations - LATRECHE, Zakaria; AKROUF , Imen (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The current article discusses modern management theories that have relied heavily on its principles to study human behavior within Organizations and try to control it, because its success depends on organizational behavior in its effective role in creating organizational culture within Economic Organizational through behavioral values, customs, traditions and norms, and trends that are emerging at the Organization level; And analysis the relationship between them and the organizational behavior by demonstrating the link between the work environment and the management of human diversity that is reflected in individual behavior. Accordingly, this study indicates that the organizational behavior has a direct impact on the management of the diversity of human resources in the Organization through its illustration within the Organizational culture which belongs to the organization that is reflected in the behavior of its human resources.